An Enhanced “Trapping−Conversion” Function Enables Ultrastable Potassium Ion Storage - Zhongquan Wang; Bangjun Wu; Zhenping Qiu; Qingguang Zeng; Aruuhan Bayaguud; Huirong Wang; Zheng Liu; Yiju Li; Yelong Zhang (Advanced Science)
Abstract Metal chalcogenides (MCs) have emerged as promising candidates for potassium ion battery (KIB) anode materials, yet the sluggish redox kinetics and notorious shuttle effect inescapability lead to inferior rate performance and poor cyclability. Herein, a P‐doped PbTe/MXene (P‐PbTe/MXene) superstructure is rationally constructed by decorating PbTe on MXene via a hydrothermal reaction and followed by bifunctional P‐doping, where P heteroatoms enter both PbTe and MXene lattice. The P‐PbTe/MXene anode shows enhanced reaction kinetics and suppressed shuttle effect of polytellurides due to the enhanced chemical adsorption stemming from the low energy gaps between the d‐band center and the p‐band center of P‐MXene. As a result, the P‐PbTe/MXene superstructure shows superior potassium storage properties, including high reversible capacity (289.1 mAh g−1 at 0.2 A g−1 after 200 cycles), outstanding rate performance (151.3 mAh g−1 at 20 A g−1), and ultrastable cyclability (180.1 mA h g−1 at 2.0 A g−1 after 2000 cycles) in half battery. Also, the P‐PbTe/MXene anode exhibits high energy density (186.0 Wh kg−1 at 0.1 A g−1) and excellent bending stability in soft‐package full cells.